1987. Impact of Updated IDSA Clostridium difficile Guidelines on the use of Fidaxomicin in a Large Health System - Bariola, J Ryan (Open Forum Infect Dis, 2019)
BACKGROUND: Fidaxomicin (fidax) is approved for treatment of Clostridioides difficile infection. In February 2018 IDSA/SHEA released updated guidelines suggesting expanded use of fidax, recommending it or oral vancomycin (po vanc) in severe or non-severe initial episodes or for most recurrences. In April 2018, University of Pittsburgh Medical Center (UPMC) relaxed system-wide guidelines to allow for fidax use in the first recurrence of C. difficile or later, with earlier use allowed by ID or GI specialists or with local Pharmacy and Therapeutics Chair approval. Hospitals could continue to be more restrictive if desired. We reviewed changes in fidax, po vanc, and IV/PO metronidazole (metro) use at UPMC hospitals after guideline changes. METHODS: For the reviewed antibiotics, hospital-level usage was evaluated at 15 UPMC hospitals before/after system-level changes. Usage was measured as days of therapy per 1,000 patient-days (DOT/1,000 PD). Sites were further grouped by the level of restrictions: Standard (following new system guidelines) or more restrictive (additional restrictions remained in place locally). Hospitals were also grouped by type of local stewardship programs (ASP): Robust (included an Infectious Diseases trained clinical pharmacist or ID physician with specific time dedicated to antibiotic review) or Non-Robust. RESULTS: Figure 1 shows before/after changes in usage at all hospitals. Figure 2 shows changes in Standard vs. More Restrictive hospitals, and Figure 3 shows changes in Robust vs. Non-Robust hospitals. CONCLUSION: Fidax use remained low, but an increase was seen after the release of the guidelines and relaxation of system restrictions, mainly in hospitals without additional restrictions in place. PO vanc also increased across the system, possibly indicating better adherence to updated guidelines regarding less metro use for C. difficile treatment. Although minimal decrease, if any, was seen with metro itself. This could have been compounded by the recent fluid shortage as well as other common uses for metro. Dissemination of new guidelines to providers should be a key function of ASPs as well as monitoring for changes in usage after implementation of local changes. Further studies are needed to define any differences in practice patterns and clinical outcomes related to changes in guidelines. [Image: see text] [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.